Complete mitochondrial genome of disc coral Turbinaria peltata (Scleractinia, Dendrophylliidae). (3rd March 2016) - Shi, Xiaofeng; Tian, Peng; Lin, Rongcheng; Lan, Wenlu; Niu, Wentao; Zheng, Xinqing
Abstract: To date, no complete nucleotide sequences of the mitochondrial genome of Dendrophylliidae are yet available. In our study, the entire mitochondrial nucleotide sequence was determined for the Dendrophylliidae species Turbinaria peltata . The sequence was 18, 966 bp in length and contained thirteen protein-coding genes, two ribosomal RNA genes ( 12S rRNA and 16S rRNA), two transfer RNA genes ( tRNA Met and tRNA Trp ) and a putative control region locating between Cyt b and ND2 . The overall base composition of the mitogenome was 25.6% A, 37.4% T, 23.5% G, and 13.5% C, with a high AT content of 63%, indicating an obvious anti-guanine bias. It shared 93.7%, 87% and 84.8 % mitogenome sequence with Goniopora columna, Acropora robusta and Euphyllia ancora, respectively.